THE EFFECTIVENESS OF BINGO GAME ON THE FIFTH GRADERSâ VOCABULARY MASTERY - Munawaroh, Nila Shofyatul (Pusat Pengembangan Bahasa, 2016)
Learning vocabulary at elementary school means the students get somevocabularies. The teacher introduces the new word to the studentsand makes the students memorize the vocabulary. Bingo Game isone of technique in teaching vocabulary. This game can be practicedby asking students to remind words they have remembered after thelesson. This study aimed at knowing the effectiveness of Bingo Gameto teaching vocabulary at elementary school. The research designof this research was pre-experimental research design by using onegroup pre-test post-test with quantitative approach. The fnding ofthis study showed that the mean score of the students after they aretaught by using Bingo Game (92.80) was higher than before they aretaught by using Bingo Game (75.60). Statistical computation usingT-test showed that the score of tcount was higher than ttable (7.247 >2.021) with standard signifcant 5% and degree of freedom was 32.It was concluded that Bingo Game is effective to teach vocabulary atelementary school.